A Chemical Survey of the Batang Belungkung River and the Gombak River - Tan, W. T.; Ng, B. S. (1980)
A chemical survey of water quality in the Batang Belungkung River and the Gombak River was conducted to assess the degree of pollution due to the continuing discharge of rubber and domestic wastes. Levels of dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), nutrients (phosphorus and nitrogen), solid and trace elements (sodium, potassium, calcium and magnesium) were monitored sequentially downriver. The Batang Belungkung River was found to be severely polluted with anaerobic conditions existing downriver. The upper region of the Gombak River was relatively unpolluted while the lower region of the Gombak River was found to be severely polluted. An increase of approximately fourteen-fold was found in the oxygen demand in the lower region of the Gombak River over the ten year period from 1968/69 to 1978/79.